Long-term risk of stroke and myocardial infarction in middle-aged men with a hypertensive response to exercise: a 44-year follow-up study. Issue 3 (9th March 2021) - Giang, Kok W.; Hansson, Per-Olof; Mandalenakis, Zackarias; Persson, Carina U.; Grimby, Gunnar; Svärdsudd, Kurt; Wilhelmsen, Lars; Börjesson, Mats; Ladenvall, Per
Abstract : Introduction: Data on the prognostic value of hypertensive response to exercise in cardiovascular disease are limited. The aim was to determine whether SBP reactions during exercise have any prognostic value in relation to the long-term risk of stroke and myocardial infarction (MI). Patients and methods: A representative cohort of men from Gothenburg, Sweden, born in 1913, who performed a maximum exercise test at age 54 years, ( n = 604), was followed-up for a maximum of 44 years with regard to stroke and MI. Results: Among the 604 men, the mean resting and maximum SBP was 141.5 (SD 18.8) and 212.1 (SD 24.6) mmHg, respectively. For maximum SBP, the risk of stroke increased by 34% (hazard ratio 1.34, 95% confidence interval 1.11–1.61) per 1-SD increase, while no risk increase was observed for MI. The highest risk of stroke among blood pressure groups was observed among men with a resting SBP of at least 140 mmHg and a maximum SBP of at least 210 mmHg with an hazard ratio of 2.09 (95% confidence interval 1.29–3.40), compared with men with a resting SBP of less than 140 mmHg and a maximum SBP of less than 210 mmHg, independent of smoking, blood glucose, cholesterol and BMI. Conclusion: Among middle-aged men with high resting and maximum blood pressure during maximum exercise workload, an increased risk of stroke was observed but not for MI. Further studies with larger sample sizes are needed to investigate the underlying mechanisms of the increased risk of stroke among individuals with hypertensive response to exercise.